Pengaruh Penjualan Air Bersih Dan Biaya Operasional Terhadap Rugi Bersih Pada Perusahaan Daerah Air Minum (PDAM) Tirta Jasa Kabupaten Lampung Selatan - Erlis Yurnita; Indah Lia Puspita; Eka Sariningsih (Universitas Malahayati, 2015)
Abstract. This research had purpose to aimed the effect of clean water selling and operational costingto net profit in perusahaan daerah air Minum (PDAM) Tirta Jasa Kabupaten Lampung Selatan.Thepopulation in this research that the annual financial report which comprises the Consolidated Profit /Loss in 2009-2013. Sample in this research is amount Consolidated Profit/Loss from 2009 until 2013,thats 60 research sampling. The data used are secondary data. Statistical method used is multiplelinear regression analysis.Based on result of this research showed that simultan and partial clean waterselling and operational costing had influence to net profit.